Spin‐Symmetry‐Selective Generation of Ultracompact Optical Vortices in Nanoapertures without Chirality. Issue 2 (9th September 2020) - Cui, Tong; Zhang, Mingqian; Sun, Lin; Zhang, Shuyin; Wang, Jia; Bai, Benfeng; Sun, Hong-Bo
Abstract : Nanoscale optical vortices (OVs) carrying orbital angular momenta can be generated via photonic spin–orbit interaction (SOI) in nanostructures and have important applications in many emerging fields such as quantum communication and optical manipulations. Existing OV generators such as metasurfaces and chiral structures suffer from discontinuous wavefront modulation, single‐spin response, and bulk size. The photonic SOI in highly symmetric structures has been overlooked. Furthermore, there is no experimental study on the near‐field formation mechanism of nanoscale OVs. Here, by studying the SOI in a plasmonic annular nanoaperture, a simple and reliable way for generating ultracompact OVs and OV array in nanoapertures without chirality is reported. The generation of a 3 × 3 OV array within a small area of 6 × 6 μm 2 is demonstrated experimentally. Using a homemade spin‐selective and phase‐resolved near‐field microscopic system, in the spin basis, the dynamic evolution of the wavefront of the generated OV is directly probed from the near field to the far field with subwavelength resolution, which intuitively reveals the SOI process. The findings provide a simple and effective solution for large‐scale, low‐cost OV beam generation and offer a powerful tool for experimental exploration of the nanoscale photonic SOI. Abstract : A simple and reliable scheme for generating nanoscale optical vortices (OVs) based on photonic spin–orbit interactions in highly symmetric plasmonic annular nanoapertures without chirality is proposed. The generation of an ultracompact OV array is demonstrated experimentally. The spatial evolution of OVs are directly probed in the spin basis by using a spin‐selective and phase‐resolved scanning near‐field optical microscope.